2012
DOI: 10.1039/c1em10678c
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating portable infrared spectrometers for measuring the silica content of coal dust

Abstract: Miners face a variety of respiratory hazards while on the job, including exposure to silica dust which can lead to silicosis, a potentially fatal lung disease. Currently, field-collected filter samples of silica are sent for laboratory analysis and the results take weeks to be reported. Since the mining workplace is constantly moving into new and often different geological strata with changing silica levels, more timely data on silica levels in mining workplaces could help reduce exposures. Improvements in inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
58
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 17 publications
3
58
0
Order By: Relevance
“…Therefore, NIOSH is evaluating field-portable technologies capable of end-of-shift (EOS) or near-realtime quantification of silica in coal dust samples. 8 This paper evaluates the use of laserinduced breakdown spectroscopy (LIBS) for that purpose.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, NIOSH is evaluating field-portable technologies capable of end-of-shift (EOS) or near-realtime quantification of silica in coal dust samples. 8 This paper evaluates the use of laserinduced breakdown spectroscopy (LIBS) for that purpose.…”
Section: Introductionmentioning
confidence: 99%
“…3 There are currently no known therapies that reduce the mortality rate of people affected with silicosis, but a simple line of defense against the disease is to monitor the amount of silica dust in the air and limit worker exposure. 5 While silicosis is easily preventable in principle, it still persists, 6,7 motivating NIOSH to investigate potential new monitoring approaches including Fourier transform infrared (FT-IR) spectroscopy, 8,9 and in the current study, LIBS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The limitations of such field-portable methods are that they are usually less sensitive than laboratory methods and are also not capable of analyzing the entire amount of material on the filter, but rather depend on localized measurements or "shots" that include only a small portion of the filter area (Chen et al 2010;Miller et al 2012). It is desirable that a potential EOS method produces results that are as close to the laboratory method as possible, while keeping the analytical method simple and easy to use in the field.…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been shown that a field-portable FTIR spectrometer could be used for relatively accurate analysis of filter samples, with potential for use as an end-of-shift (EOS) method (Miller et al 2012). The limitations of such field-portable methods are that they are usually less sensitive than laboratory methods and are also not capable of analyzing the entire amount of material on the filter, but rather depend on localized measurements or "shots" that include only a small portion of the filter area (Chen et al 2010;Miller et al 2012).…”
Section: Introductionmentioning
confidence: 99%